Reversing the “cold” tumor microenvironment: the role of neoantigen vaccines in prostate cancer - Jiani Wang; Rui Guo; Luyao Zhang; Wen Zuo; Xuan Li; Sha Zhang; Qin Tan; Jie Ma (Journal of Translational Medicine)
Abstract Background Prostate cancer (PCa) is a common malignancy with a “cold” tumor microenvironment (TME) that limits immunotherapy efficacy. Neoantigens from non-synonymous mutations are potential immunotherapeutic targets. Methods We identified the neoantigens map in the RM-1 murine prostate cancer model by the whole exome sequencing. The immunogenicity of the identified neoantigens was subsequently assessed using enzyme-linked immunospot assays. In vivo neoantigen vaccination experiments were finally conducted in mice to assess the antitumoral effect on PCa, and comprehensively understand the intrinsic dynamic mechanisms for reversing "cold" TME. Results We identified 252 nonsynonymous somatic mutations in RM-1 murine PCa, and the allele frequency of 62 mutations were above 60%. The immunogenicity and specificity of 10 candidate mutations were estimated by immunizing RM-1 mice with neoantigen peptides. Among them, four of these epitopes exhibited the immunogenicity, and three of them (Med12 D182fs , Stxbp4 A535T and Hp1bp3 L16F ) were proved to have therapeutic efficacy in the PCa murine model. Functional immunological experiments and bulk RNA sequencing indicated a significantly enhanced infiltration and activation of T cells, as well as upregulation of activated immune-related genes, and finally reversed the “cold” TME into “hot”. Conclusions This study contributed to an unmet therapeutic need for PCa, particularly its potential mechanisms for reversing “cold” TME, which lays the foundation for future application of neoantigen vaccine immunotherapy in prostate cancer.